Just go ahead...You will find the way !

Algebra Level 4

G i v e n : : S n = r = 1 n t r = n ( 2 n 2 + 9 n + 13 ) 6 Given :: \ \displaystyle S_{n}=\sum_{r=1}^n t_{r}= \frac{n(2n^{2}+9n+13)}{6} F i n d r = 1 1 r . t r Find \quad \displaystyle \sum_{r=1}^\infty \frac{1}{r.\sqrt{t_{r}}}


You can try my other Sequences And Series problems by clicking here : Part II and here : Part I.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Arif Ahmed
Oct 3, 2014

The Right Hand Side term is cubic so the t r {t}_{r} must be of degree 2 2

So one could begin by thinking over known forms such as :

r = 1 n r 2 = n ( n + 1 ) ( 2 n + 1 ) 6 \sum_{r=1}^{n}{{r}^{2}} \quad = \quad \frac {n(n+1)(2n+1)}{6}

r = 1 n r = n ( n + 1 ) 2 \sum_{r=1}^{n}{r} \quad = \quad \frac {n(n+1)}{2}

r = 1 n 1 = n \sum_{r=1}^{n}{1} \quad = \quad n

So , t r = A r 2 + B r + C {t}_{r} = A{r}^{2} + Br + C

Therefore , using the known forms and comparing the result with Right Hand Side cubic expression one should get the following system of equations :

2 A = 2 2A = 2

3 A + 3 B = 9 3A + 3B = 9

A + 3 B + 6 C = 13 A + 3B + 6C = 13

Solving one will get A = 1 , B = 2 , C = 1 A = 1 , B = 2 , C = 1

Therefore , t r = ( r + 1 ) 2 {t}_{r} = {(r+1)}^{2}

Second part is easy : r = 1 1 r ( r + 1 ) \sum_{r=1}^{\infty}{\frac {1}{r(r+1)}} = r = 1 1 r 1 r + 1 = \sum_{r=1}^{\infty}{\frac{1}{r} - \frac{1}{r+1}}

This telescopes to 1 1 .

Another way to get t r t_{r} is to see that
t r = S r + 1 S r t_{r}=S_{r+1}-S_{r}
and the rest follows....

Ishan Singh - 6 years, 8 months ago

Log in to reply

I too did it your way , just completing it

t r = S r S r 1 t_r = S_r - S_{r -1}

t r = r ( 2 r 2 + 9 r + 13 ) 6 ( r 1 ) ( 2 ( r 1 ) 2 + 9 ( r 1 ) + 13 ) 6 t_r = \dfrac{r(2r^2 + 9r + 13)}{6} - \dfrac{(r-1)(2(r-1)^2 + 9(r-1) + 13)}{6}

t r = 2 ( r 3 ( r 1 ) 3 ) + 9 ( r 2 ( r 1 ) 2 ) + 13 ( r r + 1 ) 6 t_r = \dfrac{2(r^3 - (r - 1)^3) + 9(r^2 - (r - 1)^2) + 13(r - r + 1)}{6}

t r = 6 r 2 + 12 r + 6 6 = ( r + 1 ) 2 t_r = \dfrac{ 6r^2 + 12r + 6}{6} = (r +1)^2

1 r t r = 1 r ( r + 1 ) = 1 r 1 r + 1 \dfrac{1}{r\sqrt{t_r}} = \dfrac{1}{r(r + 1)} = \dfrac{1}{r} - \dfrac{1}{r +1}

U Z - 6 years, 4 months ago

Ishaan nice one.

Nivedit Jain - 4 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...